Inter-arm blood pressure difference as a tool for predicting coronary artery disease severity. Issue 2 (12th August 2022) - Das, Somen; Iktidar, Mohammad Azmain; Das, Joyanti; Chowdhury, Faisal; Roy, Simanta
Abstract : Background: Patients with severe atherosclerosis have been found to exhibit considerable changes in blood pressure (BP) between arms. The objective of our study was to investigate the predictive value of interarm blood pressure difference (IABPD) for coronary artery disease (CAD) severity. Methods: It was a cross-sectional study conducted in the Department of Cardiology, Chittagong Medical College Hospital, Chattogram from May 2020 to November 2020. The study conveniently selected 110 individuals who visited the department for a coronary angiography during the study period. The BP of both arms were synchronously measured 1–2 days before the coronary angiography and IABPD were calculated. After coronary angiography, two blinded interventional cardiologists visually estimated the amount of coronary artery obstruction and determined the Gensini score. Results: Among the participants, more than three-fourths of the patients were above 50 years of age (64.66%), and the majority were male (86.67%). 14.7% of participants had no occlusion in their coronary artery, 38.0% of participants had insignificant occlusion, 26.7% participants had mild occlusion, 10.3% participants had moderate occlusion, 3.3% participants had significant occlusion and 6.0% participants had total occlusion. Corrected pulse IABPD (cIABPDpulse) showed the greatest area under the receiver operating characteristic curve (0.73) for predicting a high Gensini score (>median). Multiple regression analysis revealed a significant relationship between corrected systolic IABPD (cIABPDsys) and the Gensini score (B=0.057, p<0.001). Conclusion: The differences in BP between the arms were found to be having a strong positive correlation with CAD severity.